KULIAH KERJA NYATA (KKN) TEMATIK PARIWISATA “PENGEMBANGAN PARIWISATA TERINTEGRASI DI KECAMATAN SOMAGEDE KABUPATEN BANYUMAS” - Sri Lestari; Refius Pradipta Setyanto; Najmudin Najmudin (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
The purpose of College real work activities thematic tourism is for students can help the wishes of the community and the Government of sub-district somagede in developing tourism integrated in the sub-district somagede and as land of devotion for the civitas akademika Jenderal Soedirman Univercity. College real work activities thematic tourism was held in as many as three periods with Somagede involves as many as 108 students from various disciplines. Before the student was brought to the site of student provisioning process and provided with a supply of content. The implementation of activities focused on 5 areas of the program that the program includes field field 1) plan and prepare development objects and tourist attraction; preparation of human resources planning); 3) socio-economic development of the flagship; 4) development of partnerships with other institutions; and 5) promotion. Outcomes assessed work is evidenced by the existence of the Banyumas Regency Government attention began to seriously develop the tourism in the Village Kemawi Somagede and the Village of Plana as well as a highly successful of Somagede Cultural Carnival held in April 2013. The benefits of this activity is a student has experience and skills empower people in the field of tourism, cooperation Jenderal Soedirman University with various stakeholders in terms of tourism increase, reduce unemployment in sub-district somagede and raise revenue and prosperity of citizens somagede.